The Effect of Ceo Compensation, Ceo Managerial Ability, and Ceo Tenure on the Company's Financial Performance with Der as the Mediating Variable - Pitra Prasetya; Sabarudin Sabarudin; Andry Priharta (Jurnal Indonesia Sosial Teknologi, 2024)
The study aims to analyze whether CEO Compensation, CEO Managerial Ability, and CEO Tenure partially have a positive and significant influence on the Debt-to-Equity Ratio. Furthermore, to find out whether CEO Compensation, CEO Managerial ability, CEO tenure, and Debt-equity ratio have a significant and positive effect on the Return on Assets. The type of quantitative analysis method used in this study is path analysis using the help of statistic software Eviews version 12. The data used in the study is secondary data taken from the annual financial reports published on the Indonesia Stock Exchange website for 5 years (2018-2022) on 25 companies in the Consumer Non-Cyclicals sector that are listed in the BEI Period 2018 – 2022 So the amount of data on this study was 5x25 or 125 observation data. The results of this study show that (1) CEO Compensation has no positive effect on the Debt to Equity Ratio (2) CEO Managerial ability hurts debt to equity ratio (3) CEO Tenure has no negative impact on the debt-to-equity ratio (4) CEO Compensation does not have a positive influence on the Return on Assets (5) CEO Management Ability has not a positive impact on return on assets (6) CEO tenure has not had a positive effect upon the return on the assets (7) Debt on the Equity Ratio hurts returns on the Assets. (10) Debt to Equity Ratio does not mediate the influence of CEO Tenure on Return on Assets.